Effects of soaping laundering techniques to garment quality - Chicano, Anna Mikaela
Garments have always been an important part of one's everyday life, both in terms of aesthetic and function. Out of the five stages in garments life cycle, it is the "use" phase, where the garments have most environmental impact. This phase includes laundering, drying and ironing. Not only is laundering of garments wasteful to many resources, it also has a negative impact on the garment itself (Rhee, 2013). This study aimed to assess and evaluate the different laundering practices that selected Filipinos households perform and to determine their effects on the garment quality. A survey was conducted to determine the different laundering practices especially on the soaping techniques used by the selected household in UP Diliman. Convenience sampling method was used in selecting the 35 respondents of the study. It was found out that there were four different soaping laundering techniques used: hand wash only, hand wash with fishnet, hand wash with scrub brush and machine wash. These techniques were evaluated to determine their effects on the quality of the garment based on the results on dimensional stability, colorfastness to washing and pilling. After six washes, the hand wash technique showed the least effect while the hand wash with scrub brush had the greatest effect in the dimensional stability of the garments. It was also found out the hand wash only technique caused the least change in color based on the % reflectance evaluation. In addition, the machine washed garment had the highest difference in color based on the % reflectance evaluation. Hand wash is the technique that best preserved the quality of the garment after six washes based on the dimensional stability, colorfastness to washing and pilling. It had the least change in the dimensional stability and as well as, in change in color among the other techniques used in soaping. Further studies on different laundering techniques are recommended.